Hybrid Sol–Gel Silica Coatings Containing Graphene Nanosheets for Improving the Corrosion Protection of AA2024-T3 - Nasima Afsharimani; Alicia Durán; Dušan Galusek; Yolanda Castro (Nanomaterials, 2020)
In the present work, nanostructured graphene nanosheets were added to hybrid silica sols and deposited on aluminium alloy A2024-T3 to study the effect on the corrosion behaviour. Sols were prepared using tetraethyl-orthosilicate (TEOS), 3-glycidoxypropyl-trimethoxysilane (GPTMS) and a colloidal silica suspension (LUDOX) as silica precursors with adding chemically modified graphene nanosheets (GN-chem). The graphene nanosheets were modified through a straightforward and simple hydrothermal approach and then, dispersed into a silica sol (SiO2/GN-chem). ATR-FTIR was used to optimize the silica sol–gel synthesis and to confirm the cross-linking of the silica network. The corrosion behaviour of the SiO2/GN-chem coatings was also analysed by electrochemical measurement (potentiodynamic polarization) in 0.05 M NaCl solution. The results showed that the incorporation of modified graphene nanosheets into hybrid silica sol–gel coatings affected the corrosion properties of the substrates. An improvement in the corrosion resistance was observed likely due to the enhanced barrier property and hydrophobic behaviour obtained by incorporation of GN-chem and colloidal silica nanoparticles.